(untitled) - Grisham, John (New York, 2004)
A convicted rapist and murderer returns to Ford County, Mississippi, seeking revenge on the jurors who dared convict him.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy